1972
DOI: 10.1080/00039896.1972.10666043
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects of Turtle-Associated Salmonellosis

Abstract: A total of 21 reported human cases of salmonellosis implicating reptiles-turtles and one chameleon-as the most probable sources of infection were investigated in the state of Washington. Of the 103 family members, including the index cases, 48 were ill or had stool specimens testing positive for salmonellae. Salmonellae and the related arizonae were isolated from an appreciable number of turtle-lank waler samples obtained at wholesale and retail outlets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although the prevalence of Salmonella infections in freshwater turtles appears to be relatively low, the isolates include serovars, especially the serovar Muenchen, which may be involved in cases of human salmonellosis (Baker and others 1972, Fujita and others 1981). In the present study, it was shown that the turtle isolate of serovar Muenchen was able to colonise the intestinal tract of all the infected mice and chicks.…”
Section: Turtle Genus Sample Origin Number Of Isolates Salmonella Sermentioning
confidence: 99%
“…Although the prevalence of Salmonella infections in freshwater turtles appears to be relatively low, the isolates include serovars, especially the serovar Muenchen, which may be involved in cases of human salmonellosis (Baker and others 1972, Fujita and others 1981). In the present study, it was shown that the turtle isolate of serovar Muenchen was able to colonise the intestinal tract of all the infected mice and chicks.…”
Section: Turtle Genus Sample Origin Number Of Isolates Salmonella Sermentioning
confidence: 99%